Vinylidene fluoride emulsion polymerization using poly (vinyl alcohol) as sole stabilizer
By using PVOH with a high degree of hydrolysis as a stabilizer, the problem of difficulty in producing stable PVDF latex in the absence of fluorinated surfactants is solved, and the production of PVDF latex with high stability and high solid content is achieved, and the use of low molar mass surfactants is avoided.
Patent Information
- Application Number
- CN202380063327.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-25
AI Technical Summary
In the absence of fluorinated surfactants, it is difficult to produce stable PVDF latex through emulsion polymerization, and the prior art requires the use of low molar mass surfactants, affecting the stability and performance of the polymer.
Poly(vinyl alcohol) (PVOH) with a degree of hydrolysis of 70 to 99 mole % as a stabilizer is used to produce stable PVDF latex through the emulsion polymerization process of VDF, avoiding the use of fluorinated or low molar mass surfactants.
The production of stable PVDF latex in the absence of fluorinated surfactants is achieved, the stability and solid content of the polymer are improved, and the PVOH used has high degradation temperature and biodegradability as the non-fluorinated surfactants.
Smart Images

Figure SMS_1 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to a process for producing stable PVDF latex by emulsion polymerization in the absence of fluorinated surfactants, said latex being stabilized by poly(vinyl alcohol) (PVOH). Background Art
[0002] Poly (vinylidene fluoride) (PVDF) is a fluoropolymer, which is valued for its superior mechanical and thermal properties in addition to its outstanding chemical inertness. It has been used in high-performance applications such as lithium-ion batteries, coatings or water treatment. PVDF is synthesized via aqueous free radical emulsion or suspension polymerization of vinylidene fluoride (VDF). Since VDF is a gas or supercritical fluid (depending on polymerization conditions), the VDF emulsion polymerization mechanism is more complicated than most emulsion polymerization processes. In VDF emulsion polymerization, the formula includes water, VDF, a surfactant, a water-soluble initiator and optionally some additives (chain transfer agents, buffers, antiscalants). Polymerization occurs in a high-pressure reactor, wherein VDF initially exists in both the gas phase and the aqueous phase, and exists in the PVDF particles formed during polymerization.
[0003] In order to achieve stable dispersion of PVDF particles and good polymer properties, a suitable surfactant must be used. Therefore, different types of surfactants / stabilization techniques have been used industrially and / or described in the literature for VDF emulsion polymerization, such as molecular fluorinated surfactants, molecular non-fluorinated surfactants, or "surfactant-free" techniques.
[0004] Water soluble polymers (WSP) are used industrially as stabilizers in emulsion polymerization. These polymers can provide good colloidal stability through a combination of adsorption to hydrophobic surfaces and grafting to the polymer (chemically bonding the WSP to the particle).
[0005] Commonly used WSPs are hydroxyethylcellulose (paint industry) and poly(vinyl alcohol) (PVOH) (adhesive industry). The latter is used in particular as a stabilizer for the emulsion (co)polymerization of vinyl acetate to produce latexes based on poly(vinyl acetate) and has the advantage of being readily biodegradable.
[0006] PVOH polymer is synthesized by partial hydrolysis of poly (vinyl acetate) (PVAc). In addition, its colloid and interfacial properties are affected by its degree of hydrolysis (DH) and its molecular characteristics, such as molar mass or blockiness (characterized by the sequence of vinyl acetate units in the hydrolyzed polymer chain). It is well known that PVOH with a degree of hydrolysis between 70 and 90 mol % aggregates in water by intramolecular and intermolecular hydrophobic interactions of its vinyl acetate units. Due to its amphiphilic structure, it can stabilize hydrophobic particles in water by adsorption and / or grafting. The hydrophobic vinyl acetate unit provides strong adsorption on the hydrophobic particles, while the hydrophilic hydroxyl unit serves as a part for stabilization. In addition to adsorption, PVOH grafting onto particles also occurs, and it depends on chain transfer to PVOH during the polymerization of hydrophobic monomers.
[0007] The use of PVOH as a suspending agent in the suspension polymerization of VDF is known. In the absence of a suspending agent, reactor fouling can be observed.
[0008] US 2010298487 teaches the preparation of PVDF by polymerization in a dispersed aqueous medium. The aqueous suspension polymerization can be carried out in the presence of PVOH as a dispersant.
[0009] It has now been found that stabilized PVDF particles can be obtained by a process of emulsion polymerization of VDF using PVOH as the only stabilizer. Summary of the invention
[0010] According to a first aspect, the present invention relates to a process for producing a stable PVDF latex by emulsion polymerization of VDF in the absence of any surfactant that is fluorinated or of low molar mass, said process comprising the following steps:
[0011] i. loading the polymerization reactor with deionized water and stabilizer,
[0012] ii. optionally adding a chain transfer agent,
[0013] iii. optionally adding a buffer,
[0014] iv. optionally adding a paraffin antiscalant,
[0015] v. Raise the temperature to 50 to 120°C,
[0016] vi. feeding vinylidene fluoride into the reactor until the pressure reaches from 100 kPa to 10 MPa,
[0017] vii. adding an initiator to start polymerization,
[0018] viii. continuously feeding vinylidene fluoride together with optionally additional initiator to maintain said pressure,
[0019] ix. When the desired polymer conversion has been achieved, the vinylidene fluoride feed is stopped,
[0020] x. optionally continuing the initiator feed to consume the residual vinylidene fluoride,
[0021] Characterized in that the stabilizer is PVOH having a degree of hydrolysis ranging from 70 to 99 mol %, preferably from 80 to 98 mol %.
[0022] The polymeric stabilizer results in a stable PVDF latex while avoiding the need to use any fluorinated surfactants or low molar mass surfactants (typically having a molar mass below 500 g / mol).
[0023] The present invention can overcome the shortcomings of the prior art. More particularly, it provides a process for the emulsion polymerization of VDF, which allows the use of PVOH (non-fluorinated surfactant) as the only stabilizer to stabilize PVDF particles. In addition, the process according to the present invention allows the use of PVOH as a thermally stable non-fluorinated surfactant (degradation temperature above 250° C.) to prepare high-solids PVDF latex (up to 60% by weight). Advantageously, the preparation of high-solids PVDF latex uses PVOH as a biodegradable non-fluorinated surfactant. DETAILED DESCRIPTION
[0024] The present invention will now be described in detail.
[0025] According to a first aspect, the present invention provides a VDF emulsion polymerization process using PVOH as the only stabilizer for producing a stable PVDF latex (meaning it contains PVDF particles that remain dispersed at the end of the polymerization) in the absence of fluorinated surfactants or low molar mass surfactants.
[0026] PVOH is prepared by hydrolysis of PVAc and has the following formula (I):
[0027]
[0028] Formula (I)
[0029] The degree of hydrolysis is defined as DH (%) = (n / (n+m)) 100. n is the number of vinyl alcohol repeating units and m is the number of vinyl acetate repeating units in the PVOH chain. Ratio n / (n+m) 100 varies between 70 and 99 mol %, preferably between 80 and 98 mol %.
[0030] The Mw of the PVOH used in the present invention is higher than 500 g / mol: preferably higher than 1000 g / mol, more preferably higher than 5000 g / mol.
[0031] The term "vinylidene fluoride polymer" as used herein includes both conventional solid homopolymers and copolymers within its meaning. Such copolymers include those containing at least 50 mole percent of vinylidene fluoride, which is copolymerized with at least one comonomer selected from tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, pentafluoropropylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and any other monomer that is easy to copolymerize with vinylidene fluoride. The terpolymers of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene and the terpolymers of vinylidene fluoride, trifluoroethylene and tetrafluoroethylene are also representative categories of vinylidene fluoride copolymers that can be prepared by the process implemented herein.
[0032] Although the process of the present invention will be generally described with respect to the polymerization of vinylidene fluoride homopolymers, one skilled in the art will recognize that similar polymerization techniques are applicable to the preparation of copolymers of vinylidene fluoride with fluorinated or non-fluorinated co-reactive monomers.
[0033] These polymers are made through an emulsion polymerization process.
[0034] Emulsion polymerization generally involves:
[0035] - systems using emulsifiers (i.e. low molar mass surfactants) below their critical micelle concentration (thus polymerizing in the absence of micelles), or
[0036] - systems without emulsifiers (no surfactant polymerization), or
[0037] - Systems where low molar mass surfactants are replaced by reactive or non-reactive polymers.
[0038] The latter is the case for the emulsion system used in the present invention using PVOH as stabilizer for the obtained polymer particles.
[0039] During the emulsion polymerization process, the reactor is charged with deionized water, PVOH, and optionally a paraffin antifouling agent and / or a chain transfer agent.
[0040] The mixture is stirred and deoxygenated. A predetermined amount of chain transfer agent CTA is then introduced into the reactor, although CTA may not be used in this process. The reactor temperature is raised to the desired level and VDF is fed into the reactor. When the initial load of VDF is introduced and the pressure in the reactor has reached the desired level, at least one free radical initiator is added to start and maintain the polymerization reaction. VDF is optionally continuously fed with another initiator to maintain the desired pressure. The temperature of the reaction may vary depending on the characteristics of the initiator used, and those skilled in the art will know how to do so. Typically, the reactor temperature will be from 30°C to 120°C, preferably from 50°C to 120°C. The polymerization pressure may typically vary in the range of from 100 to 10000 kPa. When the desired polymer conversion has been reached in the reactor, the monomer feed will be stopped, but an initiator is optionally added to consume the residual monomer. The residual gas (containing unreacted monomer) is then discharged and the latex is collected from the reactor. The polymer can then be separated from the latex by standard methods such as freeze-thaw, spray drying, freeze drying or high shear coagulation separation.
[0041] The reaction may be started and maintained by the addition of any suitable initiator known for the polymerization of fluorinated monomers, including inorganic peroxides, "redox" combinations of oxidizing agents and reducing agents, and organic peroxides.
[0042] The free radical initiator is added to the reaction mixture in an amount sufficient to initiate and maintain the polymerization reaction at the desired reaction rate. The order of addition can vary depending on the desired process and latex emulsion characteristics.
[0043] According to an embodiment, the free radical initiator is water soluble and comprises a persulfate, such as sodium persulfate, potassium persulfate, or ammonium persulfate. The amount of persulfate added to the reaction mixture (based on the total weight of the monomers added to the reaction mixture) is from 0.005 to 1.0 weight percent.
[0044] According to an embodiment, the free radical initiator comprises an organic peroxide such as alkyl peroxide, dialkyl peroxide or diacyl peroxide, peroxydicarbonate and peroxyester in an amount from 0.5 to 2.5 weight percent of the total monomers.
[0045] Chain transfer agents are optionally added to the polymerization to adjust the molecular weight of the product. It can be added to the polymerization once at the beginning of the reaction or gradually or continuously added to the polymerization throughout the reaction. The amount and manner of addition of the chain transfer agent depends on the activity of the specific chain transfer agent used and on the desired molecular weight of the polymer product. When added, the amount of the chain transfer agent is from 0.05 to 5 weight percent, preferably from 0.1 to 2 weight percent, based on the total weight of the monomers added to the reaction mixture.
[0046] Examples of chain transfer agents useful in the present invention include, but are not limited to, oxygenates such as alcohols, carbonates, ketones, esters, and ethers; halogenated hydrocarbons and hydrohalocarbons such as chlorocarbons, hydrochlorocarbons, chlorofluorocarbons, and hydrochlorofluorocarbons; ethane and propane.
[0047] Paraffin wax or hydrocarbon oil is optionally added to the reaction to act as an antifouling agent to minimize or prevent the adhesion of polymer to the reactor components. Any long-chain saturated hydrocarbon wax or oil can play this function. The amount of oil or wax added to the reactor is an amount for minimizing the adhesion of the formed polymer to the reactor components. The amount is generally proportional to the internal surface area of the reactor, and can vary from 1 to 40 mg per square centimeter of the internal surface area of the reactor. The amount of paraffin wax or hydrocarbon oil is preferably 5 mg / cm of the internal surface area of the reactor. 2 .
[0048] Optionally, a buffer such as sodium acetate may be added to the reaction.
[0049] Advantageously, no catalyst is used in the polymerization of VDF according to the invention.
[0050] The polymerization results in a latex having a solids level of generally 10 to 60 weight percent, preferably 10 to 45 weight percent and having an average latex particle size of less than 500 nm, preferably less than 400 nm, and more preferably less than 300 nm. The average particle size is generally at least 20 nm and preferably at least 50 nm.
[0051] According to an embodiment, the latex particles of the vinylidene fluoride polymer have an average particle size comprised between 20 and 300 nm when measured by dynamic light scattering (DLS).
[0052] Small amounts of one or more other water-miscible solvents such as ethylene glycol may be mixed into the latex to improve freeze-thaw stability.
[0053] The latex of the polymer containing VDF can be dried into a powder by means known in the art, such as but not limited to spray drying, freeze drying, coagulation and drum drying. The dried powder of the polymer containing VDF can have an average particle size of from 0.5 to 200 microns, or from 1 to 100 microns, or from 2 to 50 microns, or from 3 to 20 microns.
[0054] Latexes of polymers containing VDF are suitable for the preparation of coatings, films, membranes and adhesives for battery applications.
[0055] Example
[0056] The following examples illustrate the invention without limiting it.
[0057] Examples 1-3: Emulsion polymerization of VDF in the presence of PVOH
[0058] The commercially available PVOH (M w ≈ 31 000 g mol -1 , 86.7-88.7 mol% hydrolyzed) were used as stabilizers in different experiments.
[0059] Embodiment 1: 0.20 g of potassium persulfate (KPS), 0.12 g of sodium acetate, 0.06 g of PVOH, and 100 mL of water were used.
[0060] Example 2 : Use 0.20 g of KPS, 0.12 g of sodium acetate, 0.08 g of PVOH, and 100 mL of water.
[0061] Example 3 : Use 0.20 g of KPS, 0.12 g of sodium acetate, 0.13 g of PVOH, and 100 mL of water.
[0062] The operating conditions and characteristics of these experiments and the latexes obtained are summarized in Table 1. The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0063]
[0064] a D z : Particle size measured by dynamic light scattering (DLS)
[0065] b PdI: Polydispersity Index measured by dynamic light scattering (DLS)
[0066] c M n is the number average molar mass and Ð is the dispersity. It is determined by size exclusion chromatography (SEC) in dimethyl sulfoxide (DMSO) using a calibration curve based on poly(methyl methacrylate) (PMMA) standards.
[0067] Table 1
[0068] In all cases, after one hour of reaction, a stable PVDF latex was obtained with a solid content ranging from 14.0 to 23.0% and with an average particle diameter comprised between 149 and 235 nm. The solid content decreased with increasing KPS / PVOH weight ratio, i.e. with increasing amount of PVOH. This can be explained by chain transfer reactions occurring along the PVOH chains during polymerization, causing inhibition and therefore a decrease in solid content when the amount of PVOH increases.
[0069] Example 4: Emulsion polymerization of VDF in the presence of PVOH
[0070] Commercially available PVOH (M w ≈ 130 000 g mol -1 , 86.7-88.7 mol% hydrolyzed) was used as a stabilizer, using 0.20 g of KPS, 0.12 g of sodium acetate, 0.08 g of PVOH, and 100 mL of water.
[0071] The operating conditions and characteristics of the experiments and the latexes obtained are summarized in Table 2. The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0072]
[0073] Table 2
[0074] After 1 hour of reaction, a stable PVDF emulsion was obtained with isometric particles having a diameter of 197 nm and a solid content of 19%. The particle size and solid content after 1 hour of reaction were very similar to those of Example 2 (same KPS / PVOH weight ratio), showing that the molar mass of PVOH had no significant effect on the solid content and particle size under these reaction conditions. However, the polydispersity index, molar mass and dispersity obtained in Example 4 were different from those obtained in Example 2.
[0075] Examples 5-7: Emulsion polymerization of VDF in the presence of PVOH
[0076] The commercially available PVOH (M w ≈ 13 000-23 000 g mol -1 , 86.7–88.7 mol% hydrolyzed) were used as stabilizers using different experimental conditions.
[0077] Example 5 : Use 0.20 g of KPS, 0.12 g of sodium acetate, 0.13 g of PVOH, and 100 mL of water.
[0078] Example 6 : Use 0.20 g of KPS, 0.12 g of sodium acetate, 0.08 g of PVOH, and 100 mL of water.
[0079] Example 7 : Use 0.20 g of KPS, 0.12 g of sodium acetate, 0.06 g of PVOH, and 100 mL of water.
[0080] The operating conditions and characteristics of the experiments and the latexes obtained are summarized in Table 3. The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0081]
[0082] Table 3
[0083] In all cases, stable PVDF latex was obtained after one hour of reaction.For the same amount of KPS, the solid content decreased with the KPS / PVOH weight ratio for the reasons mentioned above for Examples 1 to 3.
[0084] For the same PVOH mass and the same KPS / PVOH weight ratio, the solid content and particle size after 1 hour of reaction are very similar in Examples 2, 4 and 6, showing that the molar mass of PVOH has no significant effect on PVDF stability under these reaction conditions.
[0085] Example 8: Emulsion polymerization of VDF in the presence of PVOH
[0086] Commercially available PVOH (0.08 g, M w ≈ 9 000-10 000 g mol -1 , 80.0 mol% hydrolyzed) was used as a stabilizer, with 0.20 g of KPS, 0.12 g of sodium acetate, and 100 mL of water.
[0087] The operating conditions and characteristics of the experiments and the latexes obtained are summarized in Table 4. The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0088]
[0089] Table 4
[0090] After 3 hours 30 of reaction, a stable PVDF latex was obtained with equidistant particles of 202 nm in diameter and 31.2% solid content. The particle size was very similar to that of Example 4, but the solid content was significantly higher, showing the good PVDF stability of Example 8.
[0091] Example 9: Emulsion polymerization of VDF in the presence of PVOH
[0092] Commercially available PVOH (0.08 g, M w ≈ 31 000-51 000 g mol -1 , 98.0-98.8 mol% hydrolyzed) was used as a stabilizer, 0.20 g of KPS, 0.12 g of sodium acetate, and 100 mL of water were used.
[0093] The operating conditions and characteristics of the experiments and the latexes obtained are summarized in Table 5. The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0094]
[0095] Determination of the stable part of the sample
[0096] Table 5
[0097] After 1 h of reaction, the product obtained consisted mainly of coagulum, but the liquid and homogenous parts of the sample could be collected and analyzed gravimetrically to measure the solids content and by DLS to measure the particle size.
[0098] No stable latex can be obtained when using this PVOH for the same PVOH mass and the same KPS / PVOH weight ratio in Examples 2, 4 and 6. This may indicate that the stability of the PVDF particles depends more on the degree of hydrolysis of the PVOH than on its molar mass.
[0099] Comparative Example
[0100] Examples 10-14: Emulsion polymerization of VDF in the presence of different stabilizers
[0101] The PVDF latex obtained in the presence of PVOH was compared with PVDF latex obtained using other well-known stabilizers (Table 6).The reactor was equipped with a stainless steel four-blade stirrer and the stirring rate was 500 rpm.
[0102] Example 4 was selected for comparison, which gave particularly good results in terms of latex stability.
[0103]
[0104] Table 6
[0105] (a) Reaction conditions: 35 bar, 80 °C, 1 h reaction, 0.20 g KPS, 0.12 g sodium acetate, 0.08 g stabilizer, 100 mL water
[0106] (b) Reaction conditions: 35 bar, 80 °C, 1 h 30 reaction, 0.0088 g KPS, 0.0056 g sodium acetate, 0.15 g molecular surfactant Capstone® FS-1, 100 mL water
[0107] (c) PEG-OH (M n ≈ 2000 g mol -1 ).The stabilizing properties of PVDF are disclosed in WO2019063445.
[0108] (d) Reaction conditions: 35 bar, 80 °C, 2 h 30 reaction, 0.20 g KPS, 0.12 g sodium acetate, 0.08 g stabilizer, 100 mL water
[0109] (e) Reaction conditions: 35 bar, 80 °C, 1 h 30 reaction, 0.20 g KPS, 0.12 g sodium acetate, 0.08 g stabilizer, 100 mL water
[0110] As shown in Table 6, after 1 h of reaction, the solid content obtained in the presence of PVOH is significantly higher than the solid content that can be achieved in the presence of PEG-OH (Example 10) or in the presence of PEG-OH (Example 12), and the particles are smaller in the presence of PVOH. This shows the better stability of PVDF particles in the presence of PVOH. In addition, stable latex with a solid content higher than 15.3% can not be obtained in the absence of surfactant. Stable latex with a solid content of 20.2% and a mean particle size of 220 nm can be obtained in the presence of PEG-OH (Example 13), but can only be obtained after 2 hours 30 of reaction, and in the presence of PEG-OH, higher solid content can not be reached. In the presence of PVOH, after 1 hour 30 of reaction in the absence of condensation (Example 14), a latex with a solid content of 26.2% and a mean particle size of 230 nm can be obtained.
[0111] Finally, the latex obtained in the presence of PVOH (Example 4) was compared with the latex obtained in the presence of a molecular surfactant (FS) using the standard and reference formulations (Example 11). In the presence of a molecular surfactant, a stable latex with a solid content of 15.6% and an average particle size of 180 nm (PdI = 0.02) was obtained after 1 hour 30 of reaction. Therefore, under these reaction conditions, the use of PVOH allows to reach a higher solid content in a shorter reaction time than in the presence of FS.
Claims
1. A process for producing a stable poly(vinylidene fluoride) (PVDF) latex by emulsion polymerization of vinylidene fluoride (VDF) in the absence of any fluorinated or low molar mass surfactant, the process comprising the following steps: i. loading the polymerization reactor with deionized water and stabilizer, ii. optionally adding a chain transfer agent, iii. optionally adding a buffer, iv. optionally adding a paraffin antifouling agent, v. Raise the temperature to 50 to 120°C, vi. feeding VDF into the reactor until the pressure reaches from 100 kPa to 10 MPa, vii. adding an initiator to start the polymerization, viii. continuously feeding VDF together with optionally additional initiator to maintain the pressure, ix. When the desired polymer conversion has been achieved, stop the VDF feed, x. optionally continuing the initiator feed to consume the residual vinylidene fluoride, Characterized in that the stabilizer is poly(vinyl alcohol) (PVOH) having a degree of hydrolysis ranging from 70 to 99 mol %, preferably from 80 to 98 mol %.
2. The process of claim 1, wherein the poly(vinyl alcohol) stabilizer has the following formula (I): Formula (I), wherein in the PVOH chain, n is the number of vinyl alcohol repeating units and m is the number of vinyl acetate repeating units.
3. A process according to claim 1 or claim 2, wherein the initiator is a persulfate selected from sodium persulfate, potassium persulfate, or ammonium persulfate, and the amount of persulfate added to the reaction mixture is from 0.005 to 1.0 weight percent, based on the total weight of the monomers added to the reaction mixture.
4. The process according to any one of claims 1 to 3, wherein the initiator is an organic peroxide selected from alkyl peroxides, dialkyl peroxides or diacyl peroxides, peroxydicarbonates and peroxyesters, and is used in an amount from about 0.5 to about 2.5 weight percent of the total weight of monomers added to the reaction mixture.
5. The process according to any one of claims 1 to 4, wherein the chain transfer agent is selected from: oxygenates such as alcohols, carbonates, ketones, esters and ethers; halogenated hydrocarbons and hydrohalocarbons such as chlorocarbons, hydrochlorocarbons, chlorofluorocarbons and hydrochlorofluorocarbons; ethane and propane, and is used in an amount of from 0.05 to 5 weight percent, preferably from 0.1 to 2 weight percent, based on the total weight of the monomers added to the reaction mixture.
6. The process according to any one of claims 1 to 5, wherein the paraffin antifouling agent is selected from long chain saturated hydrocarbon waxes and oils and is used in an amount of from 1 to 40 mg per square centimeter of reactor internal surface area.
7. The process according to any one of claims 1 to 6, wherein the buffer is sodium acetate.
8. Process according to any one of claims 1 to 7, wherein the latex particles of the vinylidene fluoride polymer have an average particle size comprised between 20 and 300 nm.
9. The process according to any one of claims 1 to 8, wherein the latex particles of the vinylidene fluoride polymer have a solids content of 10 to 60, preferably 15 to 45 weight percent.
Citation Information
Patent Citations
Extrusion agent based on a heterogeneous pvdf
US20100298487A1
Synthesis of surfactant-free poly(vinylidene fluoride) latexes via raft emulsion polymerization
WO2019063445A1